Case Book for Diploma (General Dental Practice) Part I - Amarasinghe, S.R (My University, 1998)
Cyst in relation to left mandibular third molar, An extensive dentigerous ; Reconstruction of fractured incisor teeth using fractured teeth fragments; Asymptomatic mesiodenes in a nine year old child, An ; Maloccusion on skeletal base 1 with a unilateral crossbite, Treatment of angles class 1 ; Epulis in a 36 year old female patient, Management of fibrous ; Diastema, Usage of light cured composite to close a median ; Dento-alveolar infection, Management of a patient with ; Stomatitis, A recurrent aphthous ; Dry socket, Management of a case of ; Fluorosis, Endemic ; Maxillary canine under local anaesthesia, Surgical removal of an impacted right ; Edentulous patient with a complete denture prosthesi, Management of an ; Neuralgia where maxillary brach was affected, Follow up of a case of idiopathic trigeminal ; Fistula, Oro-antral; Antibiotic prophylaxis before a dental extraction of a patient with mitral valve stenosis; Cyst in the lower lip, Mucous retention ; Squanous cell carcinoma; Calculus in the submandibular region, Management of a patient with a salivary ; Treatment of class 11 division 1 case with an upper removable appliance; Von willebrand disease, Performing dental extraction in a child with